The Crime of Murder against Parents by Children - Nurbaeti, Beti; Farhana, Farhana (Budapest International Research and Critics University, 2021)
This study aims to discover, analyze, and explain the factors that cause domestic violence among children. The method used in this paper is a normative juridical approach with laws and regulations sourced from primary legal materials, a conceptual approach sourced from secondary legal materials, and a case approach—data analysis using literature study techniques. This study indicates that the factors that cause domestic violence by biological children are family, personality, social, environmental, school/educational, social media, and economic factors. Or in detail, the factors that influence violence are family financial problems, jealousy problems, child problems, parent problems, sibling problems, politeness problems, and others.